Different Fc scaffolds enhance the breadth of in vitro neutralization of the same Fab against different Rotavirus strains - Miranda-Echagüe, Mabel Rocio; Vezzani, Giacomo; Morandi, Elena; Della Peruta, Melania; Scordio, Mirko; Reyes, Teresa Anne Clarisse; Oldrini, Davide; Iturriza-Gómara, Miren; Loomis, Rebecca Jo; Rossi, Omar (Frontiers in Immunology, 2026)
Rotaviruses are the primary cause of severe dehydrating diarrhea in infants and young children globally. Currently, several oral rotavirus vaccines are available; however, they have shown reduced effectiveness and quicker waning of protection in low- and middle-income countries (LMICs) compared to high-income countries (HICs). Both neutralizing and non-neutralizing antibodies against the middle (VP6) and outer layer capsid proteins (VP4 and VP7) are detected after infection, with higher titers being linked to disease protection. Historically, human derived rotavirus-specific monoclonal antibodies (mAbs) have been produced in an IgG1 scaffold, irrespective of whether their native scaffold was IgG or IgA. To explore the impact of antibody scaffolds on their functional activity we expressed mAbs targeting epitopes on VP8* or VP7 viral proteins in IgG1, IgG2, IgG3, IgG4, IgA1, and IgA2 scaffolds (the latter either in a monomeric or in a dimeric IgA form). The mAbs were characterized for their binding affinity to the viral target and their functionality was evaluated in an in vitro neutralization assay using three different rotavirus strains (G1P[8], G2P[4], and G9P[8]), representing homologous and heterologous specificities. Our findings revealed that mAbs targeting the same epitope exhibited varying neutralization activities when expressed in different scaffolds and suggested an enhanced breadth of neutralization activity in the context of an IgA scaffold. These data suggest that scaffolds impact the ability of antibodies to neutralize rotavirus. These findings can assist vaccine design informing the use of different technologies or adjuvants to elicit more effective antibody classes and subclasses.